The effect of acupuncture on oxidative stress in animal models of vascular dementia: a systematic review and meta-analysis - Qiong-Nan Bao; Man-Ze Xia; Jing Xiong; Yi-Wei Liu; Ya-Qin Li; Xin-Yue Zhang; Zheng-Hong Chen; Jin Yao; Ke-Xin Wu; Wan-Qi Zhong; Shao-Jun Xu; Zi-Han Yin; et al. (Systematic Reviews, 2024)
Abstract Background Growing evidence showed that acupuncture may improve cognitive function by reducing oxidative stress, key to the pathogenesis in vascular dementia (VaD), but this is yet to be systematically analysed. This study aimed to summarize and evaluate the effect of acupuncture on oxidative stress in animal models of VaD. Method Eight databases including PubMed, Embase, Web of Science, Cochrane library, CNKI, Wan Fang, CBM, and VIP were searched since their establishment until April 2023, for studies that reported the effect of acupuncture on oxidative stress in VaD animal models. Relevant literature was screened, and information was extracted by two reviewers. The primary outcomes were the levels of oxidative stress indicators. The methodological quality was assessed via the SYRCLE Risk of Bias Tool. Statistical analyses were performed using the RevMan and Stata software. Results In total, 22 studies with 747 animals were included. The methodology of most studies had flaws or uncertainties. The meta-analysis indicated that, overall, acupuncture significantly reduced the expression of pro-oxidants including reactive oxygen species (standardized mean differences [SMDs] = -4.29, 95% confidence interval [CI]: -6.26, -2.31), malondialdehyde (SMD = -2.27, 95% CI: -3.07, -1.47), nitric oxide (SMD = -0.85, 95% CI: -1.50, -0.20), and nitric oxide synthase (SMD = -1.01, 95% CI: -1.69, -0.34) and enhanced the levels of anti-oxidants including super oxide dismutase (SMD = 2.80, 95% CI: 1.98, 3.61), glutathione peroxidase (SMD = 1.32, 95% CI: -0.11, 2.76), and catalase (SMD = 1.31, 95% CI: 0.05, 2.58) in VaD animal models. In subgroup analyses, acupuncture showed significant effects on most variables. Only partial modelling methods and treatment duration could interpret the heterogeneity of some outcomes. Conclusion Acupuncture may inhibit oxidative stress to improve cognitive deficits in animal models of VaD. Nevertheless, the methodological quality is unsatisfactory. More high-quality research with a rigorous design and further experimental researches and clinical trials are needed to confirm these findings. Systematic review registration This study was registered in PROSPERO (CRD42023411720).